2017
DOI: 10.1002/14651858.cd011069.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Different methods and settings for glucose monitoring for gestational diabetes during pregnancy

Abstract: Evidence from 11 RCTs assessing different methods or settings for glucose monitoring for GDM suggests no clear differences for the primary outcomes or other secondary outcomes assessed in this review.However, current evidence is limited by the small number of RCTs for the comparisons assessed, small sample sizes, and the variable methodological quality of the RCTs. More evidence is needed to assess the effects of different methods and settings for glucose monitoring for GDM on outcomes for mothers and their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 72 publications
1
58
0
1
Order By: Relevance
“…There is growing evidence in support of the impact of mHealth interventions on the management of diabetes [ 26 , 38 ]. However, given that there is as large variety of different mHealth tools currently available, the most effective method and setting for the management of GDM remain unclear [ 39 ]. A previous systematic review concluded that there was insufficient evidence showing that the use of telemedicine technology was superior to the use of the standard care procedure for women with GDM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence in support of the impact of mHealth interventions on the management of diabetes [ 26 , 38 ]. However, given that there is as large variety of different mHealth tools currently available, the most effective method and setting for the management of GDM remain unclear [ 39 ]. A previous systematic review concluded that there was insufficient evidence showing that the use of telemedicine technology was superior to the use of the standard care procedure for women with GDM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…LiP study women without a clinical diagnosis of GDM did not use SMBG, and this might be an important missing factor in our intervention group in this analysis. We have no evidence about which treatment component (diet, exercise, or SMBG) is most effective in reducing complications and regulating blood glucose (15). Similarly, we have only sparse knowledge about which type of exercise is optimal in GDM treatment (16).…”
Section: Discussionmentioning
confidence: 99%
“…GDM should be managed by a multidisciplinary team with endocrine and obstetric clinical input as well as diabetes specialist nurses and dieticians. Maternal education is key to good glycaemic control in women with GDM though there remains debate and uncertainty about the most appropriate method and frequency of home glucose monitoring and whether more frequent monitoring by continuous glucose monitoring will have additional benefits 21 . Lifestyle intervention comprising of dietary modification, physical activity and weight management is the first line treatment for GDM.…”
Section: Introductionmentioning
confidence: 99%